"Bending" Evidence for a Cause: Scholar‐Advocacy Bias in Family Law. (April 2016) - Emery, Robert E.; Holtzworth‐Munroe, Amy; Johnston, Janet R.; Pedro‐Carroll, JoAnne L.; Pruett, Marsha Kline; Saini, Michael; Sandler, Irwin
Abstract : There are a number of salient public policy issues in the family law field that have invoked impassioned policy debates on a recurrent basis. In the absence of a body of research to address these critical concerns, advocates under the guise of social science scholarship have exacerbated the confusion and controversy by construing the scant available research evidence to justify their own ends, without regard to the relevance, quality, utility, and limitations of the studies. This is one of two articles on this problem that we have named "scholar‐advocacy bias." In this article, we discuss the difference between truth in social science and truth in law. We identify common ways in which social science researchers and reviewers of research—wittingly or unwittingly—can become advocates for ideological positions and social policies at the expense of being balanced reporters of research evidence as illustrated by recent debates about overnight parenting of infants and toddlers. We also consider how adherence to established scientific principles and methods prevents the misuse of research in this way. Key Points for the Family Court Community: Scholar‐advocacy bias, the intentional or unintentional use of social science research to legitimize advocacy claims, is a problem that practitioners and policy makers must recognize and guard against in family law. Because of different methods of pursuing and establishing truth in science and the law, ironically, the less rhetorically convincing argument often represents science most faithfully. Practitioners—and scientists—must guard against using various rhetorical tactics that bend research evidence, for example, the rules of science dictate that we must prove our hypotheses; others need not disprove them.